Development of a 63K SNP Array for Cotton and High-Density Mapping of Intraspecific and Interspecific Populations of Gossypium spp. Issue 6 (1st June 2015) - Hulse-Kemp, Amanda M; Lemm, Jana; Plieske, Joerg; Ashrafi, Hamid; Buyyarapu, Ramesh; Fang, David D; Frelichowski, James; Giband, Marc; Hague, Steve; Hinze, Lori L; Kochan, Kelli J; Riggs, Penny K; et al.
Abstract: High-throughput genotyping arrays provide a standardized resource for plant breeding communities that are useful for a breadth of applications including high-density genetic mapping, genome-wide association studies (GWAS), genomic selection (GS), complex trait dissection, and studying patterns of genomic diversity among cultivars and wild accessions. We have developed the CottonSNP63K, an Illumina Infinium array containing assays for 45, 104 putative intraspecific single nucleotide polymorphism (SNP) markers for use within the cultivated cotton species Gossypium hirsutum L. and 17, 954 putative interspecific SNP markers for use with crosses of other cotton species with G. hirsutum . The SNPs on the array were developed from 13 different discovery sets that represent a diverse range of G. hirsutum germplasm and five other species: G. barbadense L., G. tomentosum Nuttal × Seemann, G. mustelinum Miers × Watt, G. armourianum Kearny, and G. longicalyx J.B. Hutchinson and Lee. The array was validated with 1, 156 samples to generate cluster positions to facilitate automated analysis of 38, 822 polymorphic markers. Two high-density genetic maps containing a total of 22, 829 SNPs were generated for two F2 mapping populations, one intraspecific and one interspecific, and 3, 533 SNP markers were co-occurring in both maps. The produced intraspecific genetic map is the first saturated map that associates into 26 linkage groups corresponding to the number of cotton chromosomes for a cross between two G. hirsutum lines. The linkage maps were shown to have high levels of collinearity to the JGI G. raimondii Ulbrich reference genome sequence. The CottonSNP63K array, cluster file and associated marker sequences constitute a major new resource for the global cotton research community.